2017
DOI: 10.1097/ftd.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Azole Plasma Trough Levels in Lung Transplant Recipients: Percentage of Therapeutic Levels and Intrapatient Variability

Abstract: Background:This study compared therapeutic azole plasma trough levels (APL) of the azole antimycotics itraconazole (ITR), voriconazole (VOR), and posaconazole (POS) in lung transplant recipients and analyzed the influencing factors. In addition, intrapatient variability for each azole was determined.Methods:From July 2012 to July 2015, 806 APL of ITR, VOR, posaconazole liquid (POS-Liq), and posaconazole tablets (POS-Tab) were measured in 173 patients of the Munich Lung Transplantation Program. Therapeutic APL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
5
27
0
Order By: Relevance
“…For all groups, more than 60% of the trough levels were in the therapeutic range, which is consistent with the findings of Stelzer et al (4). In the CFLT group, a third of the concentrations were less than 0.7 mg/liter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For all groups, more than 60% of the trough levels were in the therapeutic range, which is consistent with the findings of Stelzer et al (4). In the CFLT group, a third of the concentrations were less than 0.7 mg/liter.…”
Section: Discussionsupporting
confidence: 92%
“…The main indication for this drug is for hematological prophylaxis, but it may also be used for curative purposes and can potentially be of use in the field of lung transplants (LT), including in patients with cystic fibrosis (CF) (1,2). The rates of fungal colonization ranged from 20% to 50% in LT patients (3), a population particularly at risk for the development of fungal infections because of immunosuppressive therapy (4). This population is also at risk of fungal bronchitis, leading to abnormal healing and stenosis.…”
mentioning
confidence: 99%
“…Several studies reported CVs for the POS-tab C min , but comparing CV values is problematic since calculation methods of CV differ. Here, we used the method described by Bland (21) to calculate within-subject CV, whereas a different approach was used in other studies, i.e., the ratio between standard error and the mean POS C min in each patient (18,22). Finally, as explained above, we adjusted the POS C min for the POS dose in our cohort, which was not done in the other studies (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…Despite TDM, VRC C min are frequently out-of-the therapeutic range in clinical practice. Indeed, subtherapeutic VRC C min have been found in 20-33% of patients [6,7] and supratherapeutic VRC C min in 7-23% of cases [5][6][7][8], depending on the therapeutic threshold and study population. Although subtherapeutic VRC C min are often explained by gain-of-function single nucleotide polymorphism (SNP) *17 for CYP2C19 (at least in the Caucasian population) [9][10][11][12], comedication by enzymatic inducers [13], or non-observance [10], the determinants of supratherapeutic VRC C min have been less investigated.…”
Section: Introductionmentioning
confidence: 98%